O-031 Implementation of an Institutional-Wide Acute Stroke Algorithm: Improving Stroke Quality Metrics. (26th July 2014) - Zuckerman, S; Magarik, J; Espaillat, K; Bhatia, R; Dewan, M; Morone, P; Mocco, J
Abstract : Background and purpose: Stroke is a major public health burden in the United States. In May 2012, the Vanderbilt Emergency Department (ED) Stroke Algorithm was implemented. The goal of our study was to: 1) describe the process of revising our stroke algorithm, and 2) compare pre- and post-algorithm implementation quality improvement (QI) data. Methods: Our institutional stroke algorithm underwent extensive revision, with a focus on removing variability, streamlining care, and improving time delays. A detailed description of the Vanderbilt ED Stroke Algorithm is seen in Figure 1 . The process begins with an initial Stroke Alert page that notifies the neurology team. Immediate non-contrast head CT, routine labs, and possible CTA/CTP are obtained. After initial evaluation, a second Assessment page with NIH Stroke Scale (NIHSS) is sent. If NIHSS >6, the neurointerventionalist is immediately notified. After the case is reviewed between the neurology attending and neurointerventionalist, a third Treatment page is sent with treatment decision (none, IV tPA, IA therapy, IV tPA plus IA therapy). The following time points were assessed pre- and post-algorithm implementation: door to CT, door to neurology evaluation, and door to tPA time. Results: Our stroke algorithm was implemented in May 2012. Over four separate three-month time periods, one pre- and three post-algorithm time points, several stroke QI data points improved. The following data points improved after algorithm implementation: average door to CT time decreased from 40.4 to 13.0 min (p < 0.001); average door to neurology evaluation decreased from 34.3 to 8.3 min (p = 0.001), and average door to tPA time decreased from 67.6 to 46.5 min (p = 0.03). Conclusion: A stroke protocol was successfully implemented at our institution with promising results. Several QI parameters significantly decreased. We describe our algorithm for the benefit of other developing stroke centers in their mission to improve care of the acute stroke patient. Disclosures: S. Zuckerman: None. J. Magarik: None. K. Espaillat: None. R. Bhatia: None. M. Dewan: None. P. Morone: None. J. Mocco: None.